Penguatan Literasi Pembelajaran IPS dalam Menghadapi Perubahan Sosial Budaya Generasi Z Era 4.0 - Fatma Laili Khoirunnida; Siti Maryam Yusuf (Institut Agama Islam Negeri Ponorogo, 2022)
ABSTRACTThis study has the aim of analyzing the form of activities for strengthening social studies learning literacy in dealing with socio-cultural changes of generation Z era 4.0 in class IX A MTsN 6 Sampung Ponorogo. Analyzing the supporting and inhibiting factors for strengthening social studies learning literacy in the face of social change. As well as analyzing the changes that occurred in students after the social studies learning literacy movement in the face of socio-cultural changes. This research is a qualitative research with data collection methods of observation, interviews and documentation. Based on the results of the analysis of research data, it was found that efforts to strengthen literacy in the 4.0 era for students, the majority of which were Generation Z, were carried out with the help of several approaches such as communicative approaches, CBSA, integrative, process skills, science, society and technology. This is stated in the school literacy movement starting from early literacy, basic literacy, library literacy, media literacy, technological literacy and visual literacy. Inhibiting factors come from internal and external such as lack of motivation, environmental influences and limited facilities either at school or at each child's home. The conclusion of this study is literacy strengthening activities using forms of early literacy, basic literacy, library literacy, media literacy, technological literacy and visual literacy that bring students to be more aware and understand the importance of reading, be innovative and humanize humans today. They have now been able to instill values, norms, morals and love for local culture in themselves. In addition, they have been aware to be wise in the use of students' insights.ABSTRACTPenelitian ini memiliki tujuan menganalisis bentuk kegiatan penguatan literasi pembelajaran IPS dalam menghadapi perubahan sosial budaya generasi Z era 4.0 di kelas IX A MTsN 6 Sampung Ponorogo. Menganalisis faktor pendukung dan penghambat penguatan literasi pembelajaran IPS dalam menghadapi perubahan sosial. Serta menganalsis perubahan yang terjadi pada siswa setelah gerakan literasi pembelajaran IPS dalam menghadapi perubahan sosial budaya. Penelitian ini merupakan penelitian kualitatif dengan metode pengambilan data observasi, wawancara dan dokumentasi. Berdasarkan perolehan hasil analisis data penelitian ditemukan bahwa pengupayaan penguatan literasi era 4.0 kepada peserta didik yang mayoritas generasi Z dilakukan dengan bantuan beberapa pendekatan seperti pendekatan komunikatif, CBSA, integratif, ketrampilan proses, ilmu, masyarakat dan teknologi. Hal tersebut dituangkan dalam gerakan literasi sekolah mulai dari literasi dini, literasi dasar, literasi library, literasi media, literasi teknologi dan literasi viasual. Faktor penghambat berasal dari internal maupun eksternal seperti kurangnya motivasi, pengaruh lingkungan dan keterbatasan fasilitas baik di sekolah ataupun di rumah masing-masing anak. Kesimpulan pada penelitian ini yakni kegiatan penguatan literasi dengan menggunakan bentuk literasi dini, literasi dasar, literasi library, literasi media, literasi teknologi dan literasi viasual yang membawa peserta didik lebih sadar dan paham akan pentingnya membaca, inovatif dan saling memanusiakan maunisia saat ini. Mereka kini telah mampu menanamkan nilai, norma, moral dan cinta kebudayaan lokal kepada dirinya. Selain itu mereka telah sadar untuk bijak dalam penggunaan wawasan peserta didik.